S114 Adaptive and Innate-Like T Cell Phenotypes in Asthma in Relationship to Compartment and Severity. (19th November 2012) - Hinks, TSC; Staples, KJ; Smith, C; Ward, J; Mansour, S; Monk, P; Howarth, PH; Virgin, HW; Gadola, S; Djukanovic, R
Abstract : Introduction and Objectives: Asthma is a heterogeneous disease affecting 150–300 million people. Underlying mechanisms remain unclear. TH 17 cells expressing interleukin-17 are widely hypothesised to play a role, particularly in severe neutrophilic asthma. Mucosal associated invariant T (MAIT) cells are novel innate-like T-cells of unknown function which express CD161 and an invariant TCRα chain (Vα7.2-Jα33) and recognise the highly conserved restriction molecule MR1. We undertook to analyse IL-17 and key T-cell subsets, namely TH 17, TH 1, TH 2, TREG, and MAIT cells in relation to asthma severity and virus-induced exacerbations. Methods: Cross sectional study: 76 subjects underwent detailed phenotyping, sputum induction, phlebotomy, and bronchoscopy. Samples were analysed by 9-colour flow-cytometry, RT-PCR, multiplex ELISA, microarray, and deep sequencing of the airway microbiome. Longitudinal study: 35 frequently exacerbating asthmatics: followed at 7 time-points during a naturally occurring cold. Results: Contrary to initial hypotheses TH17 cell frequencies did not differ between health and any asthmatic phenotype, in any tissue compartment. TH2 cell frequencies were elevated in asthma in bronchoalveolar-lavage (BAL) (ANOVA p=0.041) and markedly in bronchial biopsies (p=0.048), as expected[1]. BAL TH1 cell frequencies were also increased in asthma (p=0.01) as described[2], whilst TREG frequencies were lower in severe asthma (p=0.019). TH 2 cytokines were increased in asthma in sputum (IL-5 p=0.005) and BAL (IL-5 p<0.0001, IL-13 p=0.017), but IL-17 was elevated only in BAL in steroid-naive, mild asthmatics (ANOVA p=0.04) who were older (p=0.039). Longitudinal follow-up revealed no significant differences in T-cell frequencies during exacerbations, though sputum TH 17 cells tended to increase (NS). We observed that frequencies of Vα7.2+CD161+ (MAIT) cells in blood are lower in asthma than in health (p=0.013), and correlated with severity in blood (p for linear trend <0.0001), and sputum (p=0.018, Figure 1). This deficiency is specific to MAIT cells, and is not related to age or inhaled steroid therapy. Conclusions: A role for TH17 cells in asthma, particularly severe neutrophilic disease has been widely hypothesised, but is not supported by these data. High BAL IL-17 levels in older, steroid-naive, mild asthmatics may have a different cellular source. We describe a novel finding of deficient Vα7.2+CD161+ (MAIT) cells in severe asthma. References: Robinson, DS, et al., Predominant TH2-like bronchoalveolar T-lymphocyte population in atopic asthma. N Engl J Med, 1992. 326(5): p. 298–304. Krug, N, et al., T-cell cytokine profile evaluated at the single cell level in BAL and blood in allergic asthma. Am J Respir Cell Mol Biol, 1996. 14(4): p. 319–26.